Combinatorial Tissue Engineering Partially Restores Function after Spinal Cord Injury - Hakim, Jeffrey S. (J Tissue Eng Regen Med, 2019)
Hydrogel scaffolds provide a beneficial microenvironment in transected rat spinal cord. A combinatorial biomaterials based strategy provided a microenvironment that facilitated regeneration while reducing foreign body reaction to the 3-dimensional spinal cord construct. We used poly lactic-co-glycolic acid (PLGA) microspheres to provide sustained release of rapamycin from Schwann cell (SC)-loaded, positively charged oligo-polyethylene glycol fumarate scaffolds. The biological activity and dose-release characteristics of rapamycin from microspheres alone and from microspheres embedded in the scaffold were determined in vitro. Three dose formulations of rapamycin were compared to controls in 53 rats. We observed a dose-dependent reduction in the fibrotic reaction to the scaffold and improved functional recovery over 6 weeks. Recovery was replicated in a second cohort of 28 animals that included retransection injury. Immunohistochemical and stereological analysis demonstrated that blood vessel number, surface area, vessel diameter, basement membrane collagen, and microvessel phenotype within the regenerated tissue was dependent on the presence of SCs and rapamycin. TRITC-dextran injection demonstrated enhanced perfusion into scaffold channels. Rapamycin also increased the number of descending regenerated axons, as assessed by Fast Blue retrograde axonal tracing. These results demonstrate that normalization of the neovasculature was associated with enhanced axonal regeneration and improved function after spinal cord transection.